Rendimiento escolar en comunicación en niños de 5 años de programas escolarizados y no escolarizados Red N° 10 Callao - Ledesma Dominguez de Navarro, Rosa Luz (2010)
This research is descriptive-comparative, which purpose is to establish the difference between school performance in the area of language in 5 year old children of profit schools and non – profit schools of kindergarten The PEAC-1 test was applied, a sample of 90 children of profit schools and 28 children of non – profit schools of kindergarten, belonging to the network N ° 10 of the Callao, including human settlements Gambeta, Santa Rosa and Dulanto, which lie in a lower socio - economic low,. Significant differences in comparing the results of both groups. Finding that the school performance of children of profit schools is greater than the children non – profit schools.